Pathogens of Human and Animal Infectious Diseases and their Spread in Europe by the Ixodid Tick Dermacentor Reticulatus - Podobivskiy, S.S.; Fedoniuk, L.Ya.; Andreychyn, M.A.; Marchuk, O.M.; Pavluk, T.V.; Подобівський, С.С.; Федонюк, Л.Я.; Андрейчин, М.А.; Марчук, О.М.; Павлюк, Т.В. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
Due to climate change, the possibility of human infective diseases caused by pathogens from the genera Borelia, Anaplasma, Rickettsia, Babesia, Bartonella, Coxiella, etc. is increasing in Europe. Generally, these pathogens are directly related to arthropod vectors, in particular, to Ixodes ticks. The aim of the study was to determine the current trends in the spread of tick-borne infections transmitted by Dermacentor reticulatus ticks in some European countries, including Ukraine, based on the analysis of literature. Over the past 10 years, in the vast majority of countries, including Europe, the situation with the defeat of farm and wild animals, as well as humans, by pathogens of severe infectious diseases from the genera Borrelia, Anaplasma, Rickettsia, Babesia, Theileria, Coxiella, Bartonella, Francisella, etc. has been aggravated. Representatives of these genera lead to severe diseases, such as tick-borne borreliosis, which are accompanied by damage to the central nervous system, joints, skin, and cardiovascular system. Members of the Rickettsiales genus cause a variety of feverish conditions in animals and humans. Species of the genus Babesia cause babesiosis, a disease caused by damage to red blood cells and the appearance of anti-erythrocyte antibodies, and representatives of the genus Toxoplasma cause toxoplasmosis, accompanied by damage to the nervous, lymphatic, and cardiovascular systems. Q fever is caused by species of the genus Coxiella. Severe human diseases are caused by tick-borne encephalitis viruses. Various PCR test systems have been developed and used to detect these pathogens. For example, in Poland, PCR for Borrelia burgdorferi s.l. was performed using the B. burgdorferi s.l. PCR kit (GeneProof, Czech Republic) for in vitro diagnosis. Anaplasma PCR kits (Blirt-DNA Gdańsk, Poland) were used to detect Anaplasma phagocytophilum DNA. For the detection of Babesia spp., a fragment of the 18S rDNA gene encoding a small ribosomal subunit localized in the conserved region V4 was used. To detect Bartonella spp., the tests Hum PCR Bartonella, Hum PCR Coxiella burnetii, and Vet PCR Rickettsia kit (BioIngenTech, Chile), Coxiella burnetii and Rickettsia spp. were used. In the Laboratory for the Study of Ticks and Tick-Borne Infections of Ternopil National Medical University (Ukraine), pathogens were identified using several test systems, namely DNA A. phagocytophilum, / DNA E. muris, / DNA E. chaffeensis, DNA B. burgdorferi s.l., DNA B. myamotoi; DNA Babesia sp., and RNA Ticks borne of encephalitis viruses (MolGen, Italy), which allow real-time determination on anamplifier "ROTOR Gene 6000" by Corbett Research. Studies in many European countries have shown infection of the Dermacentor reticulatus tick with the pathogens B. burgdorferi s.l. in the range from 1.6 to 49.8 %; A. phagocytophilum – 0.1–2.2 %; Babesia sрp. – 9.8–43.8 %; Coxiella spр. – 0.1–0.2%; Francisella spp. – 0.7–95%; Toxoplasma spр. – 3.2–16.7 %; and ticks borne of encephalitis viruses 8.5–16.6 %. Some Ukrainian scientists presented data on D. reticulatus infection, in particular B. burgdorferi s. l. – 10.1–22.1 %; A. phagocytophilum – 3–25.36 %; Babesia spр. – 1–41.2 %; Rickettsia sp. – 28 %; Bartonella spp. – 5 %; Coxiella spр. – 5.1 %, and tick-borne f encephalitis viruses – 11.9–71 %. The spread of many infectious agents is largely correlated with the spread of their vectors, including ticks of the D. reticulatus species. According to many scientists, this species is widespread in Europe, in particular, two metapopulations are currently distinguished as the western one, which includes the territories of France, Belgium, Slovakia, the Czech Republic, the Netherlands, and Germany, and the eastern one, which covers Lithuania, Latvia, Belarus, eastern and central Poland, and west of the Vistula River up to the Ural Mountains. In the Czech Republic, this species is found in all regions, more often in the southeastern and northwestern regions. In the UK, ticks have been found in West Wales, Devon, and Essex. In Romania, D. reticulatus was found in 17 counties, and in Moldova – in the Lower Dniester region. In Ukraine, this species is widespread from the Carpathians and Prykarpattia, Polissya, and Forest-Steppe, to the southeastern regions and Crimea.